Impact of Different Concentrations of Cinnamon Essential Oil onThe Physico-Chemical, Microbiological, and Sensory Characteristicsof Refrigerated Pork Sausages - Mounika, D; Rao, B Eswara; Babji, Y; Ambedkar, Y R; Rao, T Srinivasa (Journal of Meat Science, 2024)
The investigation examined the impact of varying concentrations of  Cinnamon Essential Oil (CEO) on the preservation of pork sausages.  The sausages were divided into different groups: a control group,0.2 µl/g  CEO (T1) 0.4 µl/g CEO (T2) and 0.6% µl/g (T3). All these samples were  stored at 4°C for 15 days. Notably, the sausages treated with 0.4 µl/g CEO  exhibited superior preservation qualities, as evidenced by lower levels  of TBARS, free fatty acids, pH, water activity, microbial count (Total  Plate Count, coliform count and staphylococcal count) and sensory  properties (colour, flavour and overall acceptability) compared to all  other treatments (p
Keywords: Cinnamon essential oil; Pork sausages; Physico-chemical properties; Microbial counts; Sensorial properties